Q methodology to define policy issues and promote stakeholder dialogue in Praia da Vitória Bay in Terceira, Azores - Maria Helena Guimar\~aes; Tomaz Ponce Dentinho; Tomasz Boski (European Regional Science Association (ERSA), 2011)
When dealing with complex issues commonly found in Coastal Zones, there is a need to find an efficient assessment strategy of processes and their causes, as well as a method which could effectively promote a dialogue with the stakeholder affected by these processes. This dialogues is an essential part of problem structuring routine since it allows mutual learning by generating and evaluating divergent knowledge claims and viewpoints. Problem structuring can start from a broad subject that is refined until the definition of a policy issue which requires a deeper analysis of its cause, as well, as possible alternatives of action. We explore the use of Q methodology as a tool for problem structuring and policy issue definition. In addition, Q methodology can be suitable for a first evaluation of the system in analysis while uncovering the several perspectives of stakeholders. We applied this methodology in Praia da Vitória Coastal System located in Terceira Island, in Azores Archipelago. The method has been applied in its original format as a method of identifying stakeholders discourse. Additionally we modified it and use it in group discussions aiming at promoting stakeholder dialogues. Results obtained show that Q methodology is an adequate to understand the value and interest of stakeholders, while adding useful information for stakeholder selection in stakeholder dialogues. The use of the method in its original format and in group session also allowed a reflection concerning the challenge of designing and promoting dialogue processes.
Keywords: 330